Budaya Menghafal Al-Qurâ€™Än: Studi Living Qurâ€™Än Masyarakat Benda Brebes Jawa Tengah - Irfan, Agus (Kopertais Wilayah X Jawa Tengah, 2018)
One of the phenomena of â€œLiving Qurâ€™Änâ€ found in Benda, Central Java is the tradition of memorizing the Qurâ€™Än. This paper presents an elaboration of the question â€œhow the contextualization step for the taá¸¥fÄ«áº“ al-Qurâ€™Än education as a solution for taá¸¥fÄ«áº“ al-Qurâ€™Än exist in Benda Bumiayu Brebes? As formulated in three Sub Question: 1. How the taá¸¥fÄ«áº“ al-Qurâ€™Än culture for Benda society can be construct as long time exist? 2. What factors that supported the taá¸¥fÄ«áº“ al-Qurâ€™Än culture exist ? 3. What factors that reduced the taá¸¥fÄ«áº“ al-Qurâ€™Än culture exist?This research is a descriptive qualitative nature, employing historical and sosiological approaches. The qualitative data are obtained through observation, interview and documentation. The data collected are then selected and arranged in a sequence with argumentative presentation.The result of this research reveal that Benda village is good known by DÄ al- Qurâ€™Än, because he has more than 7 (seven) Islamic Boarding School for memorizing Qurâ€™Än. This village used to create memorizing Qurâ€™Än culture for the society and arround him. This culture is effected by KH. KhalÄ«l Ibn Maá¸¥allÄ« dan KH. Suá¸¥aimi Ibn Abdul GhÄnÄ«, and in the second generation he has great memorizing culture. But in the third generation he gets bad value that less. AsÂ observation data, a writter has seen some fundamen factors which influence reducing the taá¸¥fiáº“ al-Qurâ€™Än culture in that village. So that needed the contextualization of taá¸¥fÄ«áº“ al- Qurâ€™Än education that switable with modernity.